Question
27. \( 2^{3 x}=4 \cdot 2^{5 x} \) 29. \( (1+x) 2^{-x}-5 \cdot 2^{-x}=0 \)
Ask by Logan George. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
**Solutions:**
- **Problem 27:** \( x = -1 \)
- **Problem 29:** \( x = 4 \)
Solution
Let's solve each of the equations step by step.
---
**Problem 27.**
\[ 2^{3x} = 4 \cdot 2^{5x} \]
**Step 1:**
Express the number 4 as a power of 2:
\[ 4 = 2^2 \]
So the equation becomes:
\[ 2^{3x} = 2^2 \cdot 2^{5x} \]
**Step 2:**
Use the property of exponents \( a^m \cdot a^n = a^{m+n} \):
\[ 2^{3x} = 2^{2 + 5x} \]
**Step 3:**
Since the bases are the same, set the exponents equal to each other:
\[ 3x = 2 + 5x \]
**Step 4:**
Solve for \( x \):
\[
\begin{align*}
3x &= 2 + 5x \\
3x - 5x &= 2 \\
-2x &= 2 \\
x &= -1
\end{align*}
\]
**Answer:**
\( x = -1 \)
---
**Problem 29.**
\[ (1 + x) \cdot 2^{-x} - 5 \cdot 2^{-x} = 0 \]
**Step 1:**
Factor out \( 2^{-x} \) from both terms:
\[ 2^{-x} \cdot (1 + x - 5) = 0 \]
**Step 2:**
Simplify inside the parentheses:
\[ 2^{-x} \cdot (x - 4) = 0 \]
**Step 3:**
Set each factor equal to zero:
1. \( 2^{-x} = 0 \)
However, \( 2^{-x} \) is never zero for any real number \( x \), so this gives no solution.
2. \( x - 4 = 0 \)
Solve for \( x \):
\[ x = 4 \]
**Answer:**
\( x = 4 \)
---
**Summary of Solutions:**
- **Problem 27:** \( x = -1 \)
- **Problem 29:** \( x = 4 \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
The Deep Dive
To solve the first equation, we can rewrite the number 4 as a power of 2: \( 4 = 2^2 \). Therefore, the equation becomes \( 2^{3x} = 2^2 \cdot 2^{5x} \), simplifying to \( 2^{3x} = 2^{2 + 5x} \). Setting the exponents equal gives us \( 3x = 2 + 5x \). Rearranging leads to \( -2 = 2x \), resulting in \( x = -1 \). For the second equation, factor out \( 2^{-x} \) to simplify: \( 2^{-x} ((1 + x) - 5) = 0 \). Since \( 2^{-x} \) cannot equal zero, we set \( (1 + x) - 5 = 0 \), which simplifies to \( x = 4 \). And voila, we've solved both equations!